What the Qur’an Rules Out: Mā Kāna Constructions and the Rhetoric of Restriction in The Qur’an - Muhammad Shohib; Muhammad Azizan Fitriana; Ade Naelul Huda; Sabri Mohamad (UIN Sunan Kalijaga Yogyakarta, 2026)
A translation that treats every Qur’anic mā kāna clause as a report that something “did not happen” misses the work performed by many of these passages. Some rule out conduct, others deny a right or autonomous power, and still others reject claims about God or the course of divine action. This article examines these differences across the Qur’an. A search of a verse-indexed Arabic text identified 213 candidate sequences; morphological and syntactic screening narrowed them to 127 negative clauses and a core of 37 instances in 36 verses. Close reading of clause structure, subject, complement, exceptions, local argument, classical grammar, iʿrāb, and tafsīr reveals no single meaning of prohibition or impossibility. Instead, the clauses restrict propositions on different grounds: communal norm, prophetic office, legitimate standing, created agency, divine permission, doctrinal propriety, divine justice, and a narrated history of refusal. Grammatical form guides these readings but does not determine them apart from context. Repeated mā kāna clauses therefore form a rhetoric of restriction: they mark what may not properly be done, claimed, attributed, or expected within Qur’anic discourse.